2021
DOI: 10.53942/srjcidi.v1i1.52
|View full text |Cite
|
Sign up to set email alerts
|

Aula Aumentada y Aula Invertida, Los Nuevos Retos en Educación Superior Universitaria

Abstract: El aula aumentada y aula invertida en cualquier nivel educativo es inminente que requiere la implementación de actividades académicas en un sistema de gestión del aprendizaje (Moodle, Chamilo, Teams, Google Classroom o Canvas). Por lo que, la finalidad de esta investigación es conocer a profundidad sobre aula aumentada y aula invertida, desarrollado mediante la descripción y explicación de investigaciones de otros autores. Se obtuvo: Primero, el análisis de los resultados de su aplicación sobre las experiencia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…In this model, students are expected to review conference materials and resources before attending class, allowing class time to be spent on discussions, problem-solving, and other interactive activities (Pardo Alean et al, 2021). Numerous studies have shown the benefits of the flipped classroom approach, including increased student engagement, increased engagement, and better overall learning outcomes (Chuquimbalqui-Maslucán, 2021;Arriaga & Medina-Talavera, 2018).…”
Section: Frame Of Referencementioning
confidence: 99%
See 1 more Smart Citation
“…In this model, students are expected to review conference materials and resources before attending class, allowing class time to be spent on discussions, problem-solving, and other interactive activities (Pardo Alean et al, 2021). Numerous studies have shown the benefits of the flipped classroom approach, including increased student engagement, increased engagement, and better overall learning outcomes (Chuquimbalqui-Maslucán, 2021;Arriaga & Medina-Talavera, 2018).…”
Section: Frame Of Referencementioning
confidence: 99%
“…In this method, students are encouraged to study the course material before attending class, allowing them to participate in interactive activities, discussions, and problem-solving sessions during class time (Arriaga & Medina-Talavera, 2018). Augmented reality adds an immersive learning experience by overlaying digital information onto the physical environment, helping students better visualize and understand complex concepts in linear machine kinematics (Chuquimbalqui-Maslucán, 2021). This approach aims to transform the traditional teacher-centered classroom into a collaborative, more studentcentered learning environment (Gonzales et al, 2023).…”
Section: Flipped Classroom With Augmented Realitymentioning
confidence: 99%
“…En este contexto, el aprendizaje invertido ha surgido como una estrategia pedagógica innovadora que invierte el paradigma tradicional de enseñanza (Álvarez & Ortiz, 2022;Cerrón y Carrión, 2022;Argüello Melo, 2023). En el aprendizaje invertido, los estudiantes acceden a los materiales de aprendizaje antes de la clase, permitiéndoles explorar conceptos por sí mismos, mientras que el tiempo de clase se dedica a actividades prácticas, discusiones y aplicaciones del conocimiento (Polanco & More, 2021), por lo que el aula invertida representa una excelente alternativa para mejorar el proceso de enseñanza aprendizaje (Chuquimbalqui-Maslucán, 2021). El paradigma de aula invertida redefine el proceso de aprendizaje al transferir la responsabilidad de la adquisición de conocimientos desde la clase presencial hacia el entorno individual del estudiante (Deng, 2023).…”
Section: Introductionunclassified